TEACHER FEEDBACK IN IMPROVING ENGLISH PROFICIENCY - Mirqodirova , Zilola Shezod qizi (GOLDEN BRAIN, 2024)
Feedback of teacher is considered to be important aspect of learning process as it sheds light on weak points of a student, helping them to improve their language skills. Effective feedback from teachers provides learners with valuable information on their language skills, helps them identify areas for improvement, and guides them towards achieving their language learning goals.